EFFECT OF SPENT ENGINE OIL ON SOIL MICRO FLORA - Okoh, Emmanuel Chidera; Ugwu, Chioma Victoria; Okenwa, Emmanuel Chukwuebuka (Advanced Journal of Environmental Sciences (AJES), 2025)
The contamination of soil by spent engine oil presents a significant environmental challenge, particularly due to its adverse effects on soil microflora, which are essential for maintaining soil health and ecosystem functionality. This study investigated the impact of spent engine oil on soil microflora by analyzing the phytochemical parameters and percentage composition of various particles in contaminated soil samples. Soil samples were examined for moisture (0.87%), pH (5.72), organic carbon (4.68%), nitrogen (0.062%), phosphorus (0.54 mg/kg), potassium (286.50 mg/kg), sodium (51.25 mg/kg), calcium (0.69 mg/kg), and magnesium (0.94 mg/kg). The texture analysis revealed sand (96.5%), silt (3.3%), and clay (0.2%). The microbial assessment showed that soil contaminated with 0 ml of engine oil had the highest percentage occurrence of fungal organisms, whereas 10 ml-contaminated soil exhibited the least occurrence. These findings highlight the negative impact of spent engine oil on soil health. Increased oil concentrations suppress fungal populations, reduce nutrient availability, and alter soil physicochemical properties. This study underscores the need for remediation strategies to mitigate the harmful effects of spent engine oil on soil microflora and overall ecosystem health